Nanoribbons with semicrystalline core dispersed in a visible-light photopolymerized epoxy network - Zucchi, Ileana Alicia (2014)
It has been well documented that self-assembly of block copolymers (BCP) in selective solvents, where the core-forming block is a crystallizable polymer, results in micelle structures with exceptional aggregation morphologies determined mainly by the crystallization energy from the core. In this contribution, we apply this concept to create ribbon-like nanostructures dispersed in an epoxy network. The selected system was a polyethylene-b-poly(ethylene oxide) (PE-b-PEO) diblock copolymer in an epoxy monomer based on diglycidyl ether of bisphenol A (DGEBA). This system was selected on the bases that PEO is an epoxy-philic block which is completely miscible with DGEBA before and after curing reaction whereas PE is a crystallizable epoxy-phobic block. Under these conditions, we access to self-assembled nanostructures with semicrystalline core before curing reaction. With the aim of preserving the structural features of these micelles, the epoxy monomers were cured at room temperature (i.e., below the melting transition of the core-forming PE block) by photoinitiated cationic ring-opening polymerization. Long nanoribbons dispersed in the cured epoxy matrix were obtained, as characterized by SAXS patterns and TEM images. These ribbon-like micelles present a tendency to aggregate resulting in the formation of face-to-face stacking of parallel micelles. We demonstrated that while the stacking number decreases with decreasing BCP concentration, the arrangement of the nanoribbons within one stack becomes less organized.